Average Error: 0.0 → 0.0
Time: 5.5s
Precision: 64
$\left(x + y\right) - \frac{\frac{x}{y}}{2}$
$\left(x + y\right) - \frac{\frac{x}{y}}{2}$
\left(x + y\right) - \frac{\frac{x}{y}}{2}
\left(x + y\right) - \frac{\frac{x}{y}}{2}
double f(double x, double y) {
double r2101664 = x;
double r2101665 = y;
double r2101666 = r2101664 + r2101665;
double r2101667 = r2101664 / r2101665;
double r2101668 = 2.0;
double r2101669 = r2101667 / r2101668;
double r2101670 = r2101666 - r2101669;
return r2101670;
}


double f(double x, double y) {
double r2101671 = x;
double r2101672 = y;
double r2101673 = r2101671 + r2101672;
double r2101674 = r2101671 / r2101672;
double r2101675 = 2.0;
double r2101676 = r2101674 / r2101675;
double r2101677 = r2101673 - r2101676;
return r2101677;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(x + y\right) - \frac{\frac{x}{y}}{2}$
2. Final simplification0.0

$\leadsto \left(x + y\right) - \frac{\frac{x}{y}}{2}$

# Reproduce

herbie shell --seed 1
(FPCore (x y)
:name "x+y - ((x/y)/2)"
:precision binary64
(- (+ x y) (/ (/ x y) 2)))